2001
DOI: 10.1074/jbc.m100383200
|View full text |Cite
|
Sign up to set email alerts
|

Gcn2 Mediates Gcn4 Activation in Response to Glucose Stimulation or UV Radiation Not via GCN4 Translation

Abstract: In mammalian cells transcription factors of the AP-1 family are activated by either stress signals such as UV radiation, or mitogenic signals such as growth factors. Here we show that a similar situation exists in the yeast Saccharomyces cerevisiae. The AP-1 transcriptional activator Gcn4, known to be activated by stress signals such as UV radiation and amino acids starvation, is also induced by growth stimulation such as glucose. We show that glucose-dependent Gcn4 activation is mediated through the Ras/cAMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 52 publications
2
26
1
Order By: Relevance
“…This transient induction in a nutritional shift-down is impaired in a mutant containing low, constitutive PK A (PKA) activity, suggesting that PKA activation is required for the response (21). Consistently, mutants with hyperactive PKA function (bcy1 and RAS2 val ) show constitutively derepressed GCN4 translation that is at least partly independent of Gcn2p (21,59). It is not understood how high-level PKA activity induces GCN4 translation independently of eIF2␣ phosphorylation, except that it depends on the uORFs in GCN4 mRNA.…”
Section: Gcn2p-independent Induction Of Gcn4 Translationmentioning
confidence: 68%
See 1 more Smart Citation
“…This transient induction in a nutritional shift-down is impaired in a mutant containing low, constitutive PK A (PKA) activity, suggesting that PKA activation is required for the response (21). Consistently, mutants with hyperactive PKA function (bcy1 and RAS2 val ) show constitutively derepressed GCN4 translation that is at least partly independent of Gcn2p (21,59). It is not understood how high-level PKA activity induces GCN4 translation independently of eIF2␣ phosphorylation, except that it depends on the uORFs in GCN4 mRNA.…”
Section: Gcn2p-independent Induction Of Gcn4 Translationmentioning
confidence: 68%
“…The readdition of glucose would allow the translation of GCN4 mRNA to proceed without a further increase in the level of eIF2␣ phosphorylation. Gcn4p levels are very low in cells grown on the rich medium used by these workers (59), and a small, transient increase in Gcn4p levels sufficient to account for the induction of Gcn4p target genes by glucose refeeding may have been difficult to detect. High salinity is another situation where increased eIF2␣ phosphorylation failed to stimulate GCN4 translation until several hours had elapsed, and this result was attributed to severe inhibition of all translation during the lag period in salt-stressed cells (25).…”
Section: Regulation Of Gcn4p Functionmentioning
confidence: 99%
“…One of the differences between SP1 and ͚1278b genetic backgrounds is the more active Ras pathway in ͚1278b. Cells of the ͚1278b genetic background were shown to contain higher cAMP levels, to induce constitutive Gcn4 activity, and to suppress the cellular stress response (16,30). All those characteristics are known to be associated with an active Ras pathway (3, 5,7,17,25,27).…”
Section: Resultsmentioning
confidence: 99%
“…Four protein kinases are known to phosphorylate Ser-51 in eIF2␣ in response to different stress stimuli as follows: (i) the dsRNA-activated protein kinase PKR that is activated by dsRNA produced during viral infection (20); (ii) the general control of nitrogen metabolism kinase GCN2 that responds to amino acid depletion (22); (iii) the heme-regulated inhibitor kinase that responds to heme deprivation (23); and (iv) PERK that responds to the accumulation of unfolded proteins in the endoplasmic reticulum as well as to glucose depletion (24,25). Previous studies demonstrated that PERK and GCN2 can mediate translational inhibition through the phosphorylation of eIF2␣ in response to UV light irradiation (11,26,27). However, the roles of PERK and GCN2 in UV light-induced translation inhibition are a source of controversy.…”
Section: Discussionmentioning
confidence: 99%